A Review on Current Knowledge of Medicinal Properties of Garcinia quaesita - Srikokulan, Sivasinthujah; Nirubini, A. S. (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Garcinia quaesita is an endemic plant to Sri Lanka, has garnered attention from traditional medicine practitioners and researchers due to its diverse medicinal properties. G. quaesita have been traditionally used to treat conditions like fevers, fractures, hyperlipidemia, wounds, and hemorrhoids. This review amalgamates data from scientific papers, ayurvedic texts, and other sources. It provides information on its botanical descriptions, phyto-constituents, antioxidant, antibacterial, anti-hyperglycemic, anti-inflammatory, cytotoxic and anticancer activities. There have been few studies that reported the medicinal properties of the leaf, fruit rind and fruit. The presences of phytoconstituents such as alkaloids, glycosides, flavonoids, saponins, tannins, terpenoids, polyphenolics, coumarins, phytosterols, betacyanin, quinones were found as the responsible for the medicinal properties, Notably, the presence of garcinol was one of the responsible compounds for the bioactivity of G. quaesita. This all-encompassing review accentuates the diverse aspects of medicinal property of G. quaesita and its chemical composition, facilitates the identification of novel pharmaceutical products.